2012
DOI: 10.1071/an11357
|View full text |Cite
|
Sign up to set email alerts
|

Production traits and hatching of a Barred Rock 1 pure line, its feather sexable strains and their crosses

Abstract: The study was carried out to identify some production traits of the pure Barred Rock 1 (BR1) line and rapid × slow feathering line crosses derived from the BR1 pure line, in addition to F1 crosses of all these dam lines with Rhode Island Red 1 sire line. The BR1 line previously used a brown layer dam line for barred/non-barred day-old chick auto-sexing and synthetic slow and rapid wing feathering lines. Parent lines showed significant differences in sexual maturity and egg production (P < 0.01) and early em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
1
0
0
Order By: Relevance
“…(2011) reported that medium size eggs of Potchefstroom keokeok chicks had the highest hatchability than large and small eggs size group. The results of this study is also supported by that of Durmus (2010) who reported that fertility, late embryonic mortality (dead in shell), and hatchability differed between genotypes.…”
Section: Discussionsupporting
confidence: 88%
“…(2011) reported that medium size eggs of Potchefstroom keokeok chicks had the highest hatchability than large and small eggs size group. The results of this study is also supported by that of Durmus (2010) who reported that fertility, late embryonic mortality (dead in shell), and hatchability differed between genotypes.…”
Section: Discussionsupporting
confidence: 88%